Competencies of Education for Sustainable Development Related to Mathematics Education in Senior High School. (July 2019) - Yuniarti, Yuyun Sri; Hasan, Rusman; Ali, Mohammad
Abstract: Education for Sustainable Development (ESD) is an idea which developed since 1992 as a concept of development that bases 3 pillars as its foundation: environment, social and economic. School is one of the educational media to be a strategic place to develop this concept. Teachers as someone who has an important role in learning must understand this concept. Therefore, this study aims to analyze teachers perceptions to education for sustainable development and analyzing the competencies in the dimensions of ESD that can be integrated into the curriculum of mathematics. The study was conducted using a survey method with questionnaires to 107 mathematics teachers of senior high school in the West Java and Banten grouped according to the geographical location. Data analysis was carried out through descriptive statistics and one way anova using SPSS. The results of the study provide two conclusions: first, the geographical location does not affect the teachers perception, second, almost all competencies in the dimensions of ESD can be integrated into the curriculum of mathematics.